Contentious Storytelling Online: Articulating Activism through Negotiation of Metanarratives. (August 2020) - Gonzalez, Victoria
Narratives are one of the primary ways that activists communicate online and as this study shows, they also prove to be a major source of contention. Analysis of two digital social justice campaigns—the #Wearethe99% narratives (associated with the Occupy Wall Street Movement) and the #BelieveinSwanQueen narratives (associated with the Swan Queen Movement)—suggests that strategies of contentious narrative development online largely involve the negotiation of metanarratives. The online narratives appear to rely upon metanarratives as a foundation for expressing broad societal grievances and personal opinions and struggles. The two dominant strategies for expressing grievances throughout the discourses are the (1) reclaiming and (2) rejecting of "The American Dream" (#Wearethe99%) and "Once Upon a Time" (#BelieveinSwanQueen) metanarratives. The negotiation of these metanarratives has led to the development of an alternative "anti-story, " which serves as narrative structure to navigate both personal and social issues.